Resting Physiological Correlates of Reduced Exercise Capacity in Smokers with Mild Airway Obstruction. (4th May 2017) - Elbehairy, Amany F.; Faisal, Azmy; Guenette, Jordan A.; Jensen, Dennis; Webb, Katherine A.; Ahmed, Rashid; Neder, J. Alberto; O'Donnell, Denis E.; ,
ABSTRACT: Smokers with minor spirometric abnormalities can experience persistent activity-related dyspnea and exercise intolerance. Additional resting tests can expose heterogeneous physiological abnormalities, but their relevance and association with clinical outcomes remain uncertain. Subjects included sixty-two smokers (≥20 pack-years), with cough and/or dyspnea and minor airway obstruction [forced expiratory volume in one-second (FEV1 ) ≥80% predicted and >5th percentile lower limit of normal (LLN) (i.e., z-score >−1.64) using the 2012-Global Lung Function Initiative equations]. They underwent spirometry, plethysmography, oscillometry, single-breath nitrogen washout, and symptom-limited incremental cycle exercise tests. Thirty-two age-matched nonsmoking controls were also studied. Thirty-three (53%) of smokers had chronic obstructive pulmonary disease by LLN criteria. In smokers [ n = 62; age 65 ± 11 years; smoking history 43 ± 19 pack-years; post-bronchodilator FEV1 z-score −0.60 ± 0.72 and FEV1 /FVC z-score −1.56 ± 0.87 (mean ± SD)] versus controls, peak oxygen uptake (̇VO2 ) was 21 ± 7 vs. 32 ± 9 ml/kg/min, and dyspnea/̇VO2 slopes were elevated (both p < 0.0001). Smokers had evidence of peripheral airway dysfunction and maldistribution of ventilation when compared to controls. In smokers versus controls: lung diffusing capacity for carbon monoxide (DL CO) was 85 ± 22 vs. 105 ± 17% predicted, and residual volume (RV)/total lung capacity (TLC) was 36 ± 8 vs. 31 ± 6% (both p < 0.01). The strongest correlates of peak ̇VO2 were DL CO% predicted ( r = 0.487, p < 0.0005) and RV/TLC% ( r = −0.389, p = 0.002). DL CO% predicted was also the strongest correlate of dyspnea/̇VO2 slope ( r = −0.352, p = 0.005). Ins mokers with mild airway obstruction, associations between resting tests of mechanics and pulmonary gas exchange and exercise performance parameters were weak, albeit consistent. Among these, DLCO showed the strongest association with important outcomes such as dyspnea and exercise intolerance measured during standardized incremental exercise tests.